EXTRALINGUISTIC ISSUES IN INTERCULTURAL COMMUNICATION (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the role of extralinguistic issues in intercultural communication, emphasizing how communication extends far beyond language itself. It focuses on a range of non-linguistic factors—including non-verbal communication, contextual understanding, power distance, cultural norms and values, ethnocentrism, stereotypes, time orientation, and cultural adaptability—that significantly shape communication dynamics across cultures. The study argues that successful cross-cultural interaction depends not only on linguistic competence but also on the ability to interpret and respond to these underlying cultural elements. Particular attention is given to attitudes, rituals, and traditions as key extralinguistic components influencing intercultural communication.
Keywords: Intercultural communication, extralinguistic factors, cultural attitudes, rituals, traditions, non-verbal communication, cultural values, cross-cultural interaction